2014
DOI: 10.2478/s11532-014-0535-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro hemocompatibility and corrosion behavior of new Zr-binary alloys in whole human blood

Abstract: The aim of this study is to evaluate the accuracy of three binary alloys’ composition, and their biocompatibility. Depending on the intended use of the medical devices made from these materials, dynamic or static tests should be performed. We have chosen static tests as we thought they may be used as knee or hip replacement, and not as cardiac valves.Three binary alloys ( Zr10Nb, Zr2.5Nb and Zr12Ta) were obtained from high purity powders (>99.9%), using an induction furnace first, and an electric arc furnac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…41 As proposed by Totea et al, depending on the hemolysis percentage, materials can be classified into three categories: materials resulting in over 5% hemolysis are hemolytic, between 5% and 2% are slightly hemolytic, and below 2% are nonhemolytic. 42 Hemolytic activity measurements revealed that independently of the concentration used, all tested polymers show hemolytic activity around 1% ( Figure 5A). This makes them very attractive materials for the formation of drug carriers applied via intravenous injection.…”
Section: Biological Studies Hemocompatibility Studies Of Pnipaam Derimentioning
confidence: 96%
“…41 As proposed by Totea et al, depending on the hemolysis percentage, materials can be classified into three categories: materials resulting in over 5% hemolysis are hemolytic, between 5% and 2% are slightly hemolytic, and below 2% are nonhemolytic. 42 Hemolytic activity measurements revealed that independently of the concentration used, all tested polymers show hemolytic activity around 1% ( Figure 5A). This makes them very attractive materials for the formation of drug carriers applied via intravenous injection.…”
Section: Biological Studies Hemocompatibility Studies Of Pnipaam Derimentioning
confidence: 96%
“…The absorption of CMH is measured at 540 nm using a photometer. Depending on hemolysis, materials can be classified in three different categories: Materials resulting in over 5% hemolysis are classified hemolytic, between 5 and 2% as slightly hemolytic, and below 2% as nonhemolytic (Totea et al, 2014 ).…”
Section: Determination Of Blood Cell Numbers and Hemolysismentioning
confidence: 99%
“…Hemocompatibility refers to the compatibility to blood and is another critically important requirement for implant materials. The hemocompatibility of three Zr-X alloys, Zr-10Nb, Zr-2.5Nb and Zr-12Ta, in human blood have been assessed and found acceptable, [44] which confirms the compatibility of Zr-alloys. Zr-coated Ti alloy implants resulted in enhanced cell responses in the early stages due to improved wettability.…”
Section: Bioactivity Of Zrmentioning
confidence: 62%